A Case of Delayed Encephalopathy after Carbon Monoxide Poisoning Longitudinally Monitored by Diffusion Tensor Imaging - Kuroda, H.; Fujihara, K.; Takahashi, S.; Shinozawa, Y.; Itoyama, Y. (American Journal of Neuroradiology, 2012)
SUMMARY: A woman with DE after CO poisoning was longitudinally evaluated by DTI, performed during the following periods: at the phase of acute CO poisoning, the lucid interval, neurologic deterioration due to DE, and neurologic recovery. The present case revealed the long-term course of DTI parameters after CO poisoning and the usefulness of DTI for quantifying neurologic damage after CO poisoning. ADCapparent diffusion coefficientCOcarbon monoxideDEdelayed encephalopathyDTIdiffusion tensor imagingFAfractional anisotropyGCSGlasgow Coma ScaleHBOhyperbaric oxygen therapyWMwhite matter